Pengaruh Media Sosial terhadap Penggunaan Bahasa Gaul di Kalangan Mahasiswa Universitas Muhammadiyah Maumere - Yusfina Tuto; Katharina Woli Namang (Protasis: Jurnal Bahasa, Sastra, Budaya, dan Pengajarannya, 2024)
This article aims to describe the influence of social media on the formation and spread of slang among students at Muhammadiyah University, Maumere. Social media, such as Instagram, TikTok, and Twitter, are not only a means of interaction, but also a major catalyst in creating and disseminating new terms. This phenomenon reflects students’ linguistic creativity and is also a reflection of the dynamics of digital culture. In the context of Maumere Muhammadiyah University students, the use of slang is not just a trend, but also a tool to adapt to a dynamic social environment. New terms that are popular on social media are often adopted in daily conversations as symbols of modern and contemporary identity. However, this phenomenon also raises challenges, especially related to the preservation of formal language and traditional values in communication. This article discusses the characteristics of slang that emerges from social media, its role in forming social identity, and its impact on the use of formal language. In conclusion, social media plays a significant role in shaping student communication patterns, but efforts are needed to maintain a balance between language creativity and the use of standard language in formal contexts.